"Buy-It-Now" or "Sell-It-Now" Auctions: Effects of Changing Bargaining Power in Sequential Trading Mechanisms - Tim Grebe; Radosveta Ivanova-Stenzel; Sabine Kröger (Institute for the Study of Labor (IZA), 2015)
We study experimentally the effect of bargaining power in two sequential mechanisms that offer the possibility to trade at a fixed price before an auction. In the "Buy-It-Now" format, the seller has the bargaining power and offers a price prior to the auction; whereas in the "Sell-It-Now" format, it is the buyer. Both formats are extensively used in online and offline markets. Despite very different strategic implications for buyers and sellers, results from our experiment suggest no effects of bargaining power on aggregate outcomes. There is, however, substantial heterogeneity within sellers. Sellers who ask for high prices not only benefit from having the bargaining power but also earn revenue above those expected in the auction.
Keywords: C72; C91; D44; D82; 330; Buy-It-Now price; Sell-It-Now price; private value auction; single item auction; sequential selling mechanism; fixed price